Impact of a pharmacist in extended role on an acute mental health ward. Issue 3 (9th August 2022) - Shepherd, Neil; Beveridge, Ed; Parker, Caroline
Abstract : Specialist mental health pharmacist roles are recognised in providing medicines optimisation for people with mental health disorders. Here, the authors describe an initiative that examined whether a pharmacist could fulfil the role of an 'extended role practitioner' on an acute psychiatric ward, so releasing consultant psychiatrist clinical time. The study considers how extended roles such as advanced clinical practitioner can be utilised and service provision redesigned around new patient‐facing roles.